A "Requalificação" do patrimônio: intervenções, estratégias e práticas na Praça dos Mártires (Passeio Público) de Fortaleza - Lopes, Francisco Willams Ribeiro (2013)
This research analyzes the policies of heritage preservation specifically designated as “requalification” in Fortaleza, state of Ceará, Brazil. As a part of such policies, interventions are carried out especially in historic sites considered as “degraded” with the aim of transforming them in sites of entertainment and leisure. Based on the interventions implemented in the historic center of Fortaleza, this research takes to the spotlight the public square Praça dos Mártires, also known as Passeio Público. Registered as a heritage site by the National Institute of Historic and Artistic Heritage (IPHAN), at the end of the 20th century it rose to prominence as a “degraded” equipment due to its deteriorated infrastructure and to its use, as it was largely used by prostitutes for practices of sexual commerce, encounters and socialbilities. Beginning in 2007, the site became subject to a project of “requalification” carried out by authorities of the Fortaleza Secretariat of Culture (Secultfor) through the production of events and activities seeking to replace “old” with “new” users. The strategic measures implemented, actors and social practices featuring such processes of change are presented in this work. From the standpoint of an “ethnographic observation”, I present a mapping of uses of this heritage site in the context of “requalification” policies, aiming to verify to what extent such strategic measures approximate to the practices of the multiple and heterogeneous users of these historic sites. Thus, I point out that such urban interventions do not contribute for constituting a public space in the city of Fortaleza.